Behind every stroke survivor: a bibliometric visualization of caregiver stress in rehabilitation - Bidhan Dolai; Avradeep Bose; Hriddhiman Basu; Sayan Roy (Cybrarians Journal, 2025)
Carers, frequently family members, are crucial to the recovery process after a stroke, which is a significant global health problem. Given that carers' health directly affects the degree of care provided to stroke survivors, understanding the challenges they confront is essential as the prevalence of stroke rises. It is believed that this research would enhance carer support, ultimately assisting stroke survivors.